Effect of Exercise and Antidepressants on Skeletal Outcomes in Adolescent Girls With Anorexia Nervosa - DiVasta, Amy D.; Feldman, Henry A.; O'Donnell, Jennifer M.; Long, Jin; Leonard, Mary B.; Gordon, Catherine M. (Journal of adolescent health, 2017)
We examined the relationships between malnutrition, lifestyle factors, and bone health in anorexia nervosa (AN) via dual-energy X-ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT). Seventy adolescent girls with AN and 132 normal-weighted controls underwent pQCT tibial measures including trabecular volumetric bone mineral density (vBMD), cortical vBMD, and cortical thickness. Participants with AN underwent DXA measures of the axial skeleton. We assessed the association of DXA and pQCT measures with clinical and lifestyle variables. Body mass index Z-score and ideal body weight percentage were positively correlated with trabecular vBMD, cortical CSA, and section modulus (p < .04). Exercise was associated with all pQCT measures but only with hip BMD by DXA. In AN, the use of antidepressants was associated with lower pQCT measures (p < .03). Antidepressants may negatively, and exercise positively, influence BMD in adolescents with eating disorders. These findings offer a provocative look at two longstanding questions.